2010
DOI: 10.1039/c000900h
|View full text |Cite
|
Sign up to set email alerts
|

NaKA sorbents with high CO2-over-N2 selectivity and high capacity to adsorb CO2

Abstract: The uptake of carbon dioxide and nitrogen gas by zeolite NaKA was studied. A very high ideal CO(2)-over-N(2) selectivity and a high CO(2) capacity were observed at an optimal K(+) content of 17 at.%. NaKA is a very promising adsorbent for CO(2) separation from water-free flue gases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
196
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(218 citation statements)
references
References 28 publications
20
196
1
1
Order By: Relevance
“…These 'trapdoor' 3 zeolites adsorb CO 2 from mixtures of CH 4 or N 2 with very high selectivity. Zeolites A 18,19 and chabazite 20,21 with particular cation compositions have been suggested to demonstrate such behaviour, as have certain forms of zeolite Rho [22][23][24] and structures related to Rho. 25,26 In zeolite Rho, 27 large lta cages are linked by double 8-ring structural units, which act as windows and are also the favoured sites for large univalent cations such as Na + , K + and Cs + (8-ring refers to a ring of 8 framework metal atoms and 8 oxygen atoms).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 'trapdoor' 3 zeolites adsorb CO 2 from mixtures of CH 4 or N 2 with very high selectivity. Zeolites A 18,19 and chabazite 20,21 with particular cation compositions have been suggested to demonstrate such behaviour, as have certain forms of zeolite Rho [22][23][24] and structures related to Rho. 25,26 In zeolite Rho, 27 large lta cages are linked by double 8-ring structural units, which act as windows and are also the favoured sites for large univalent cations such as Na + , K + and Cs + (8-ring refers to a ring of 8 framework metal atoms and 8 oxygen atoms).…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Recent computational studies have demonstrated that extraframework cations can move in the presence of CO 2 , 17 making cation gating effects possible. [18][19][20][21][22][23][24] In the postulated 'trapdoor' mechanism, cations occupying window sites permit the passage of molecules such as CO 2 or H 2 O that interact strongly with cations but block the windows to molecules that interact more weakly (such as CH 4 or N 2 ). These 'trapdoor' 3 zeolites adsorb CO 2 from mixtures of CH 4 or N 2 with very high selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, moderate selectivity for CO 2 over N 2 or CH 4 can be achieved over cationic zeolites such as Na-X [4] or Na-A [5], which result from the quadrupole moment of CO 2 and its polarisability. Recently, however, small pore zeolites of specific structures and compositions have been found to show very high selectivity for CO 2 over less polar gases such as CH 4 and N 2 due to a molecular 'trapdoor' effect that makes them strong candidates as sorbents for carbon capture [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Assim, seria impossível a manutenção da vida como ela é conhecida. 1 A concentração de GEE na atmosfera pode ser alterada por causas naturais como erupções vulcânicas, queimadas ou ainda pela ação do homem (antropogênica). Segundo o quarto relatório do Painel Intergovernamental sobre Mudanças do Clima (IPCC), as concentrações dos três principais gases de efeito estufa  metano (CH 4 ), óxido nitroso (N 2 O) e gás carbônico (CO 2 )  tiveram um grande aumento desde 1750, e hoje, ultrapassam significativamente os valores pré-industriais determinados pelos testemunhos de gelo de milhares de anos.…”
Section: Gases De Efeito Estufaunclassified